P111 Insulin-like Growth Factor 1 and risk of depression in older people. (13th September 2016) - Chigogora, S; Zaninotto, P; Kivimaki, M; Steptoe, A; Batty, GD
Abstract : Background: Depressive disorders are a leading cause of disability in older age. While the role of psychosocial and behavioural predictors has been well-examined, little is known about the biological origins of depression. Findings from animal studies suggest a link between Insulin-like Growth Factor 1 (IGF-1) and depression. Mice whose Insulin-like Growth Factor 1 (IGF-1) was knocked out using viral vectors displayed increased symptoms of depression, while IGF-1 infusions had an antidepressant effects on depressed mice. Human studies of this association have so far yielded conflicting results. In the present study, we examined the association of IGF-1 with both self-reported depression symptoms and physician diagnosis of depression. Methods: In 6, 017 adults (mean age of 65.7 (SD = 9.3); range 50–99) from the English Longitudinal Study of Ageing, serum levels of IGF-1 were measured during a nurse visit in 2008 (mean 15.9, SD = 5.7). Depression symptoms were assessed in 2008 and 2012 using the eight item Centre for Epidemiological Studies Depression Scale (CES-D) (mean 1.2, SD = 1.8). Multivariable logistic regression analyses were used to test associations. Results: The main finding of this study of was that having IGF-1 levels in the lowest and highest quintiles was associated with a slightly higher risk of depression symptoms in older people. With the lowest risk apparent at median levels of IGF-1, a 'U'-shaped relationship was therefore observed in some analyses. In men, using the lowest quintile of IGF-1 as the referent, the age-adjusted odds ratios (95% confidence interval) of developing depression symptoms after four years of follow-up, for increasing quintiles of IGF-1, were: 0.51 (0.28–0.91), 0.50 (0.27–0.92), 0.63 (0.35–1.15) and 0.63 (0.35–1.13) (P-value for quadratic effect 0.002). Statistical significance was not achieved for all levels of IGF-1. Similar results were observed for women, and for the relationship between IGF-1 and physician diagnosed depression. These associations were partially attributable to co-morbidities, psychosocial and behavioural factors, and adverse socioeconomic circumstances. Conclusion: In the present study of older adults, there was some evidence that moderate levels of IGF-1 levels conferred a reduced risk of depression. Paucity of data in this field justifies further investigation.